Effect of Chitin in Shrimp Meal on Growth Performance and Digestibility in Growing Broilers - Sutisa Khempaka; Masato Mochizuki; Katsuki Koh; Yutaka Karasawa (The Journal of Poultry Science, 2006)
In order to clarify whether chitin in shrimp meal (SM) affects growth performance of broilers adversely, body weight gain, feed intake, digestibility and nitrogen retention were measured in broilers given diets containing 3 levels of SM and chitin. In addition, meat and skin color was also measured in the expectation of color intensification by astaxanthin in SM. Body weight gain, feed intake and feed efficiency decreased numerically in birds given SM diets, but did not change in birds given chitin diets. Dry matter (DM) digestibility decreased with increasing levels of SM and chitin. Chitin digestibility was low (at most 24%) and tended to decrease with increasing levels of SM and chitin. Ash digestibility decreased with increasing levels of SM but unchanged with increasing levels of chitin. N retention decreased with increasing levels of SM and chitin. The redness of thigh meat was increased by feeding SM. In conclusion, the results obtained here showed that decreased DM digestibility observed in birds given SM diets seemed to be explained by the low digestibility of chitin in SM, and SM may be useful to improve meat color of broilers.